Mesoscale Variability, Critical Latitude and Eddy Mean Properties in the Tropical South‐East Atlantic Ocean. Issue 3 (14th March 2023) - Halo, Issufo; Raj, Roshin P.; Korosov, Anton; Penven, Pierrick; Johannessen, Johnny A.; Rouault, Mathieu
Abstract: Equatorward decrease of mesoscale eddy abundance, and meridional variations of their mean properties in the tropical South‐East Atlantic Ocean have been investigated on the basis of horizontal length‐scales of geostrophic flows, and theories of two‐dimensional geostrophic turbulence on a β ‐plane. Meridional variations of satellite‐derived altimetric eddy kinetic energy density spectra were assessed in bins of 5°, from 5°S to 25°S, zonally averaged between 8°W and 15°E. They revealed two latitudinal bands of minimum eddy energy spectra: one in the northern Angola Basin (5°S–10°S) and the other across the Angola Benguela Front (15°S–20°S). In the latter, both the eddy forcing scale and the Rhines scale were observed at wavelengths of 300 and 350 km respectively, suggesting that only a small spectral range exists for eddies to grow. On the other hand, in the former, the eddy forcing scale and the Rhines scale were observed at wavelengths of 454 and 520 km respectively. The ratio between the Rhines scale and the first baroclinic Rossby radius revealed an onset of a critical latitude at about 11.4°S. Consistently, maps of eddy frequency of occurrence computed from eddies identified in the region has shown a notable decay in signal of the eddy density distribution around that latitude. This could explain the sharp equatorward transition of mesoscale processes observed in this region, which seems to shift from nonlinear eddies to linear Rossby waves, potentially explaining why fewer eddies are observed in the region when compared to other regions of the world oceans. Plain Language Summary: In this study we analyzed oceanic flow variability across the range of oceanic intermediate length‐scale (∼10–400 km). We show that at about 11.4°S oceanic processes at intermediate scale shifts equatorward from a vortex‐dominated to wave‐dominated regimes. Such transition seems to provide answers to why relatively fewer vortex‐structures are usually found in the tropical South East Atlantic Ocean when compared against similar regions of the world oceans. The census conducted on the vortex population in the region revealed that their prevalence increased poleward, statistically consistent with the increase of the vortices ability to conserve their structures more effectively. Key Points: Two latitudinal bands of minimum eddy energy spectra were found in the study region and appear to limit the eddies growth in size A critical latitude emerged around 11°S and suggests a transition of mesoscale regimes from nonlinear eddies to linear waves Eddy nonlinearity and lifespan increased poleward with decreasing size and the anticyclones trapped more chlorophyll than the cyclones